Study of localized shear fracture mechanisms in alloys under dynamic loading - Sokovikov, Mikhail Al’bertovich; Chudinov, Vasiliy Valer’yevich; Oborin, Vladimir Aleksandrovich; Uvarov, Sergey Vital’yevich; Naimark, Oleg Borisovich (Computational Continuum Mechanics, 2019)
The split Hopkinson - Kolsky bar was used to perform dynamic tests on АМг6 alloy samples during target perforation. Thermodynamics of the deformation process was investigated to identify the characteristic strain localization stages through in-situ recoding of temperature fields with the infra-red camera CEDIP Silver 450M. Temperature measurements made in the localization zone have not provided sufficient evidence for the traditional strain localization mechanism occurred due to thermoplastic instability. In order to study the phenomenon of plastic strain localization with the split Hopkinson-Kolsky bar, a series of dynamic experiments were carried out on specially developed samples made of АМг6, Д16 and Steel 3 alloys using the StrainMaster system, which offers non-invasive shape, strain and stress measurements. Displacement and strain fields were constructed for the samples made of АМг6, Д16 and Steel 3 alloys tested under dynamic loading using the split Hopkinson - Kolsky bar. A comparison between the experimentally obtained temperature and strain fields and the numerical simulation results gained taking into account the distinguishing features of meso-defect accumulation kinetics shows that they agree well with accuracy to 20%. The surface relief of the special shaped samples obtained experimentally was examined with the aid of an optical interferometer-profiler New-View 5010 and by performing 3D deformation relief data processing. These studies made it possible to calculate a scale invariant (Hurst index) and the spatial scale of the region, where the correlated behavior of defects can be observed. Based on the experimental results, the data of studying deformed sample surfaces and the results of numerical simulations performed taking into account the kinetics of meso-defect accumulation, we can suggest that one of the mechanisms responsible for plastic strain localization under high-speed loading conditions is caused by the jump-wise changes in the defect structure of materials.